From Insult to Injury : How Disputes Begin and Escalate among Adolescents and Young Adults in Medellin, Colombia (2013)
ABSTRACT: This article aims to contribute to the understanding of circumstances, causes of initiation, and process of escalation of physical disputes or fights resulting in physical injury. We analyzed data from a case-control study of perpetrators of violence between the ages of 15 to 24 (n=373) in the city of Medellín, Colombia. The findings show that 89% of conflicts resulting in injury took place in public places and most often involved males (78%). Six percent involved the consumption of alcohol, 20% reported having used illicit drugs before the initiation of the confrontation. Circa 50% of disputes began because of verbal aggression. Alcohol consumption was found to be associated with verbal aggression towards a friend or companion but not to other circumstances that start disputes. Drug use was not associated with the initiation of disputes. In 18.5% of the cases, a weapon was used while 5% of these disputes ended in a homicide. In none of the cases in which homicide was the outcome was there bystander intervention. In contrast, homicide did not result in the cases in which bystanders intervened.